PEMANFAATAN WEB BLOG SEBAGAI MEDIA PEMBELAJARAN MATEMATIKA DI SMK NEGERI 1 PUJER TAHUN PELAJARAN 2020/2021 - Ageng Jely Purwanto (FKIP Universitas Jember, 2021)
The Covid 19 pandemic has caught the attention of many parties, especially in the education sector. Teachers must always innovate in developing media for the implementation of the distance learning process. One of the media that can be used is a web blog. A web blog is an alternative media that is easy for teachers to make and easy for students to use. Students who are the research subjects are XI grade and XII grade with a classroom action research model. From the results obtained, it appears that students can make good in using of the media, as evidenced by the 100% complete assignment of students even though in daily tests the completeness of the students is less than 50%. This is because students are not familiar with the AKM questions model